The Politics of Feminist Foreign Policy and Digital Diplomacy - Aggestam, Karin; Rosamond, Annika Bergman; Hedling, Elsa.; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2024)
The overarching aim of the book is to provide the first comprehensive account of Sweden$1 (Bs feminist foreign policy and its dissemination through digital diplomacy. In contrast to other scholarly studies of digital diplomacy that tend to view it as a technological and apolitical device for online diplomatic communication, this book examines the specific political dynamics of digital diplomacy. It posits that digital diplomacy is a highly political practice and form of communication. The book offers an in-depth examination of the interdependent relationship between digital diplomacy and feminist foreign policy, with an empirical focus on Sweden. Additionally, it introduces a novel theoretical framework to analyse the political characteristics of digital diplomacy, emphasising the oscillation between antagonism and agonism at the intersection of feminist foreign policy and digital diplomacy. In sum, the book provides new theoretical and empirical knowledge of why, how, and in what ways power-political dynamics are produced, sustained, and transformed within the contexts of feminist foreign policy and digital diplomacy. While the focus centres on Sweden, the authors contend that their novel approach to examining the political dynamics of digital diplomacy and feminist foreign policy applies to other country case studies as well. This is an open access book. Karin Aggestam is Professor in Political Science at the Centre for Advanced Middle Eastern Studies at Lund University Annika Bergman Rosamond is Senior Lecturer of International Relations and Gender at the University of Edinburgh Elsa Hedling is Associate Senior Lecturer in European Studies at the Centre for Languages and Literature at Lund University She is also an Associate Research Fellow at the Swedish Institute of International Affairs in Stockholm. .s
Chapter 1: Introduction -- Chapter 2: The Politics of Feminist Foreign Policy and Digital Diplomacy.-Chapter 3: Leadership, Digital Diffusion and Feminist Foreign Policy -- Chapter 4: Nation Branding, Digital Advocacy and Feminist Foreign Policy -- Chapter 5: Visuality, Digital Visibility and Feminist Foreign Policy -- Chapter 6: Conclusion: Beyond Feminist Foreign Policy and Digital Diplomacy.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: International relations; Political science; Diplomacy; Foreign Policy; International Relations; Politics and International Studies; Diplomacy; Political Science